일부 대기업 근로자의 보조구강관리용품 사용실태와 교육요구도 조사 - 박신영; Sin Young Park; 이흥수; Heung Soo Lee (Han'guk Ch'iwisaeng Hakhoe chi, 2014)
Objectives : The purpose of the study is to develop a program of oral health education byinvestigating the use and educational needs on auxiliary oral care products in employees. Methods : A self-administered questionnaire was filled out by 321 employees in the heavyindustry in Youngam-gun. Results : Most of the employees used the dental floss. Approximately 72.6% answered thatthey did not receive the education on auxiliary oral care products and 81.3% of subjects didnot participate in the education for the auxiliary oral care products. If free education is provided,66.5% would receive the auxiliary oral care products use education. The best ways of educationwere expert lecture and brochure. Conclusions : The employees want the continuing education for the use of auxiliary oralcare products. The oral health promotion program must be focused on the active practice oforal health behavior.